2022
DOI: 10.11591/ijere.v11i4.22847
|View full text |Cite
|
Sign up to set email alerts
|

The scientific argumentative skill analysis reviewed from the science literacy aspect of pre-service teacher

Abstract: <span lang="EN-US">Scientific argumentative skills could encourage the critical thinking skill of college students about scientific phenomena. This research aimed to measure and describe the scientific argumentative skill of the primary school teacher candidates, reviewed from the scientific literacy. This research applied the quantitative method by using a survey typed cross-sectional design. The researchers selected the participants with convenience sampling. The results were 184 college students of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Based on the analysis of keyword relationships, the fourth cluster discusses the application of TAP related to contextual problem-solving in improving scientific literacy. Research from (Fakhriyah et al, 2022), the scientific argumentation measurement pattern could be found by using TAP.…”
Section: Visualization Of Results Using Vosviewersmentioning
confidence: 99%
“…Based on the analysis of keyword relationships, the fourth cluster discusses the application of TAP related to contextual problem-solving in improving scientific literacy. Research from (Fakhriyah et al, 2022), the scientific argumentation measurement pattern could be found by using TAP.…”
Section: Visualization Of Results Using Vosviewersmentioning
confidence: 99%
“…The active participation of students who have the courage to convey the results of their thoughts will indirectly increase their intellectual development [10]; [11]. With scientific argumentation skills, a student is able to develop this when they have a high conceptual understanding [12]. The ability to argue scientifically equips students to be able to think critically through extracting information, empirical evidence to support an opinion, and verifying the data or information they receive.…”
Section: Introductionmentioning
confidence: 99%
“…Research on inquiry learning models using three types of structured inquiry learning, guided inquiry learning models and open inquiry in improving scientific argumentation skills in fluid material is important because scientific argumentation skills are one of the high-level thinking skills needed in the era of globalization (Frey et al, 2015). Scientific argumentation skills can help students to develop conceptual, critical, creative and reflective understanding of scientific phenomena (Fakhriyah et al, 2022). The use of fluid material is because it is a complex and abstract material, so it requires in-depth understanding and broad application.…”
Section: Introductionmentioning
confidence: 99%